Changes in the Number of Public Health Nurses Employed in Local Governments in Japan During the Covid-19 Pandemic: A Cross-Sectional Study. (November 2022) - Taira, Kazuya; Hosokawa, Rikuya; Shiomi, Misa
Introduction: Prefectural public health centers in Japan conducted epidemiological surveys of all COVID-19 patients, which subsequently increased their workload as the infection rate increased. The survey was conducted by public health nurses (PHNs); therefore, an increase in their workload was expected. However, changes in the number of PHNs have not yet been examined. This study focused on recruiting PHNs to local governments in Japan during the COVID-19 pandemic. Methods: This cross-sectional study of 150 local government public health centers was conducted from November to December 2021. The survey items included the number of full-time and part-time PHNs, number of PHNs who resigned or retired from the job, and number of PHNs recruitment examinations conducted between 2017 and 2021. For all variables, the mean, standard deviation, and minimum and maximum values for each municipality and year were calculated, and a one-way analysis of variance was performed. Conclusion: The response rate of the questionnaires was 54.0% (81/150). The change in the employment status of PHNs from 2019 to 2020 was not statistically significant in 2020, which was the COVID-19 outbreak year. However, the number of full-time PHNs increased by 2.6, while part-time PHNs almost doubled from 5.2 ± 8.3 to 10.8 ± 9.6 ( p  = .61) for prefectures, from 13.6 ± 13.1 to 21.5 ± 34.8 ( p  = .23) for cities, and from 16.8 ± 26.8 to 52.3 ± 132.5 ( p  = .70) for wards. The survey revealed that since the COVID-19 pandemic, the ratio of part-time to full-time PHNs significantly increased. Current status reports of public health centers will encourage political decisions and research on the factors necessary to balance the supply and demand of full-time PHNs.